Pengaruh Peran Key Opinion Leader (KOL) Dalam Meningkatkan Brand Awareness Hotel INNSiDE By Melia Yogyakarta - Natasya Azaria Talita Putri; Titik Akiriningsih; Afiefah Sulistyowati (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2025)
A Key Opinion Leader (KOL) is someone who is recognized as an expert or has special characteristics that have a social influence on other people. This study aims to determine the influence of Key Opinion Leaders (KOL) on increasing brand awareness of Hotel INNSiDE by Melia Yogyakarta, as well as to analyze how to select Key Opinion Leaders (KOL) who align with the characteristics of Hotel INNSiDE by Melia Yogyakarta. The research method is qualitative, using data collection techniques such as interviews, observations, documentation, and literature reviews. The sources used in this study were 2 people, including the Marcom Manager and the Graphic Designer. The data analysis used triangulation. The results of the study show that Key Opinion Leaders (KOLs) have a significant influence on increasing brand awareness of Hotel INNSiDE by Melia Yogyakarta.